Effect of story maps on EFL students’ achievement in writing narrative texts - Fardhila Sheli Rahmawati; Bambang Yudi Cahyono; Mirjam Anugerahwati (Journal on English as a Foreign Language, 2018)
The purpose of this study was to investigate the effect of story maps used in process-approach on the achievement in writing narrative texts of junior high school students as perceived from their learning styles. A quasi-experimental design was implemented in seven meetings. Two existing second-grade classes of a junior high school in Malang City, East Java, Indonesia were selected to be experimental and control groups. The students in the experimental group were taught by using story maps when they followed process approach in writing narrative texts, while those in the control group were taught in the conventional method which was conducted through writing notes. There were 20 students in the experimental group and 13 students in the control group. Independent t-test was used to analyze the scores of both groups. The finding indicated that the difference is significant between the students’ scores in the experimental group and those in the control group in favor of the experimental group. The result also revealed that there is no significant difference in the achievement in writing narrative texts between the visual and auditory learners.